Penerapan Metode Penemuan Terbimbing pada Pembelajaran Matematika Siswa SMP - Riyadi, Agusman; Mulyono, Dodik; Purwasi, Lucy Asri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the completeness of mathematics learning outcomes for Class VIII students of SMP Negeri 8 Lubuklinggau after the guided discovery method is applied. The research method used was quasi-experimental with a population of class VIII as many as 191 students and as a sample was class VIII F as many as 32 students taken randomly. Data collection was carried out using test techniques in the form of essay questions. The collected data were analyzed using t-test. Based on the results of data analysis on confidence level Î± = 0.05, it was found that t-count > t-table with a value of 5.18> 1.69 The average value of students before applying the guided discovery method was 21.83 and after giving the guided discovery method is 81.27 with the percentage of students who complete reaches 83.3%. Conclusion, the application of the guided discovery method in mathematics learning is significantly proven to be able to improve the average grades of Grade VIII students of SMP Negeri 8 Lubuklinggau. Keywords: Guided Discovery, Learning Outcomes, Mathematics